Evaluation of different Maximum Allowable Deficit (MAD) levels for rice under raised bed planting and flat sowing in Pakistan - Iqbal, Shahzad; Si, Qiaorui; Ali, Asad; Wang, Jian; Abid, Muhammad; Adnan Shahid, Muhammad (Cogent food & agriculture, 2025)
Efficient water management in rice cultivation is crucial due to global freshwater scarcity and the need for sustainable agriculture. Freshwater scarcity is a growing global concern, and Pakistan, a water-scarce country, faces further reductions in available water. This study examined the effects of different Maximum Allowable Deficit (MAD) levels on rice growth and yield under raised bed and flat sowing methods. The experiment was conducted at the Water Management Research Centre, Faisalabad, Punjab, Pakistan, using a Randomized Complete Block Design with three replications and six treatments. Flat (conventional) and bed sowing methods were compared, with irrigation scheduled at MAD levels of I1 = 0%, I2 = 20%, and I3 = 40% during the 2021 and 2022 rice seasons. Treatments T4(I1) and T5(I2) used 3236 and 3248 m³ ha−1 of water, respectively, compared to T1(I1) and T2(I2) with 4022 and 4040 m³ ha−1. The highest water productivity was recorded under T4(I1) (2.94 kg m−3), with T5(I2) (2.90 kg m−3) statistically at par. Bed planting saved 28.06% more water than flat sowing. The current study advances sustainable agriculture by optimizing water use in rice cultivation, showing that raised bed-planting with controlled irrigation enhances water productivity and yield.